THE RELATIONSHIP BETWEEN STUDENTS’ PERSONALITY AND SPEAKING PERFORMANCE - Dewi Aulia Hardiyanti; Hasanul Misbah; Muhamad Sofian Hadi (Eltin Journal : Journal of English Language Teaching in Indonesia, 2021)
The purpose of this research is to find the relationship between extrovert and introvert personality and speaking performance of students in class XI Imam Bukhori SMK IT Multimedia An-Nuqthah, Tangerang, Banten. This research method is used as a quantitative correlation study. The population and sample are 21 students of SMK IT Multimedia An-Nuqthah, using simple random sampling in class. A questionnaire is used to determine the student’s personality type, and a test is used to determine the student’s speaking performance. The personality questionnaire and the speaking test scores are correlated by using the Pearson product moment formula. The result of  is higher than  in 5% (0, 9984 > 0, 4329) and 1% (0, 9984 > 0, 5487). The conclusion of this research there is the relationship between students' personality and speaking performance. It is hoped that this research will help achieve goals and success, and also help to be more effective in the process of English teaching. Keywords: personality, extrovert, introvert, speaking